Antiinflammatory Activity of Aqueous Bark Extract of Butea monosperma (Lam.) Taub. - Nautiyal, Vinod; Kumar, Ashwani; Thapliyal, Somesh; Kumar Goel, Kapil (Asian Journal of Chemistry, 2011)
Butea monosperma is used in the traditional system of medicine for treating inflammation, tumors, diabetes anticonvulsant, antidiarhoeal, etc. Present study emphasizes its efficacy against inflammation. The bark was collected from its natural habitat care was taken to select healthy plant for normal bark. Aqueous bark extract of Plaso monosperma was tested to study the effect on the inflammation using the technique of carrageenan induced paw edema in the abino rats. It is concluded that aqueous bark extract showed significant antiinflamatory activity compare to the reference standard indomethacin. It was found that the aqueous bark extract (200 mg/kg) showed significant activity (p < 0.001) at 2 and 3 h when compared to standard but it has been found that the dose of 200 mg/kg aqueous bark extract showed good activity as compare to dose of 100 mg/kg aqueous bark extract.